Pengaruh Komunikasi Interaktif dan Motivasi Guru terhadap Prestasi belajar siswa dalam Pembelajaran Pendidikan Agama Islam di SMPN 2 Semende Darat Tengah Muara Enim Sumatera Selatan - Hayani, Jumra; Lubis, Mawardi (Al-Bahtsu: Jurnal Penelitian Pendidikan Islam, 2024)
The aim of the research is to determine the effect of interactive communication and teacher motivation on student learning achievement in PAI learning at SMPN2 SDT Muara Enim SUMSEL. To determine the effect of teacher motivation on student learning achievement in PAI learning at SMPN2 SDT Muara Enim SUMSEL; To determine the influence of interactive communication and teacher motivation on student learning achievement in PAI learning at SMPN2 SDT Muara Enim SUMSEL. The type of research used is quantitative. The data collection techniques used are observation, questionnaires and documentation. Based on the research results, it is known that there is a significant influence between interactive communication and teacher motivation on student learning achievement in PAI learning at SMPN2 SDT Muara Enim SUMSEL. This is proven by the results of the analysis that the t-count is > than the t-table, namely the t-count is 11.021 while the t-table is 0.6775. This means that student learning achievement in subject matter can be determined by interactive communication carried out by the teacher in the learning process. There is a significant influence between teacher motivation and student learning achievement in PAI learning. This is proven by the analysis results obtained by t-count > t-table, namely t-count is 10.214 and t-table is 0.6675. There is a significant influence between interactive communication and teacher motivation on student learning achievement in PAI learning. This is proven by the analysis results obtained by F-count of 8.275 with an f-table of 2.75. This means F-count > f-table (8.275 > 2.75).